The Roles of Antisociality and Neurodevelopmental Problems in Criminal Violence and Clinical Outcomes Among Male Forensic Inpatients - Hilton, N. Zoe (Criminal justice and behavior, 2018)
Research has identified developmental pathways linking childhood abuse and poor parenting to cognitive impairment or general antisociality in adolescence. We examined pathways in adult offenders, aiming to reproduce pathways identified in the limited existing research with male forensic inpatients and testing their robustness and relation to clinical outcomes. Using structural equation modeling (SEM), we examined antisociality, neurodevelopmental problems, and antisocial parenting as statistical predictors of criminal violence, in 638 cases. Using exploratory factor analysis and SEM, we developed and tested similar models for health status on admission and institutional outcomes (symptoms and aggressive behaviors) in subsamples of 269 and 335 cases. A three-factor measurement model was obtained, replicating previous work and supporting antisociality and neurodevelopmental problems as pathways to criminal violence and poor adult health. Models of institutional outcomes were not well supported. Findings indicate robustness of antisocial development and neurodevelopmental pathways.